In Situ Polymerization of Long Alkyl Chain Functional Groups Enhances the Oil–Water Separation Performance of Porous Organic Polymers - Hongbo Zhao; Shijie Cai; Ruoting Hua; Cong Li; Chunlong Xia; Bo Cui; Huimin Shao; Naishun Bu; Ye Yuan (Molecules)
The preparation of superhydrophobic functional materials is of great significance for applications in oil pollution control. However, the materials synthesized by traditional post-modification methods usually suffer from problems of limited active sites, uneven distribution, and susceptibility of the surface structure to external factors, which may significantly affect their superhydrophobic properties. In this study, the superhydrophobic porous organic polymer LNU-32 was successfully prepared via in situ polymerization with the introduction of green, low-surface-energy, long-alkyl-chain functional groups into the pores, which formed a “brush-like” structure on the pore surface of the polymer and effectively enhanced its hydrophobicity. The LNU-32 material exhibits excellent superhydrophobicity, with a water contact angle of more than 151°. In addition, the superhydrophobic polyester fabric prepared from LNU-32 has an oil–water separation efficiency of more than 90%. The adsorption capacity of the superhydrophobic fabric for dimethicone also reached 7.37 times its own weight. The study shows that the LNU-32 material exhibits good application potential in the field of oil–water separation, especially in the treatment of oily wastewater and oil spills.